Paving the path towards efficient construction logistics by revealing the current practice and issues - Ahmet Anil Sezer; Anna Fredriksson (Logistics, 2021)
Multiple deliveries and long turnaround times on construction sites harm the environment and disturb on-site productivity and safety. The purpose of this paper is to investigate the transport patterns of construction material deliveries, including turnaround times. In order to investigate the number of transports and turnaround times, transport data for 13 Swedish construction sites, which were collected with the help of booking systems, were used. By comparing data from the cases, several patterns were observed: (i) very few projects receive deliveries at weekends, (ii) almost all projects receive 50% of their daily deliveries before 09:00, (iii) long goods, standard euro pallets and lightweight goods (less than 500 kg) are the most common deliveries, (iv) trucks and delivery vans are the most common vehicles used and (v) goods to be handled by crane and lightweight goods generate the longest turnaround time/delivery. This is one of the rare studies revealing current practice and issues associated with material deliveries, which is a necessary first step to increase efficiency of construction logistics. This study shows that it is possible to influence these issues, as some projects performed better than others regarding turnaround times and transport.
Keywords: 650; construction sites; construction transport; efficiency; turnaround times